Vortioxetine improves symptomatic and functional outcomes in major depressive disorder: a novel dual outcome measure in depressive disorders - М. С. Christensen; Н. Loft; R. S. McIntyre (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Summary. With symptomatic remission and functional recovery as the overarching therapeutic objectives of antidepressant therapy, composite endpoint measures that conjointly consider both aspects of treatment are needed. This analysis evaluated the combined eﬀect of vortioxetine on depressive symptoms and functional capacity in adults with MDD.Methods: NCT01564862, a multinational, double-blind, placebo-controlled, duloxetine-referenced study, con-ducted between April 2012 and February 2014, in 602 adult outpatients (18–65 years) with moderate-tosevere MDD (Montgomery-Asberg Depression Rating Scale (MADRS) ≥ 26), a major depressive episode of ≥ 3 months’ duration, and self-reported cognitive symptoms were randomized to once-daily vortioxetine (10 or 20 mg), duloxetine (60 mg), or placebo for 8 weeks. Assessments included the University of California San Diego Performance-based Skills Assessment (UPSA) and the MADRS. Two versions of UPSA were utilized; UPSA ‒Validation of Intermediate Measures and UPSA Brief form. An aligned UPSA-B (communication and finance items) was examined for sensitivity analysis. Eﬃcacy was analyzed versus placebo according to the dualresponse (change from baseline in UPSA ≥ 7 and ≥ 9 and reduction in MADRS total score from baseline ≥ 50%).Results: Significantly more vortioxetine-treated patients were classified as dual responders for change in MADRS total score and UPSA score of ≥ 7 (clinically important diﬀerence [CID]) (27.4% vs 14.5%; P = 0.004), and change above CID (≥ 9) (23.4% vs 13.9%; P = 0.025). Duloxetine did not diﬀer significantly from placebo for these dual response criteria. Sensitivity analysis using the aligned UPSA-B confirmed these results for vortiox-etine.